Menguatkan Transformasi Digital Melalui Kepemimpinan Transformasional: Peran Mediasi Keterlibatan Pegawai dan Kompetensi Digital pada BKD Provinsi Banten - Agus Surya Mulyana; Ahmad Mukhlis; Angrian Permana (Jurnal Publikasi Ilmu Manajemen, 2026)
The purpose of this study is to analyze the direct influence of Transformational Leadership, Employee Engagement, and Digital Competence on Digital Transformation and the indirect influence of Transformational Leadership on Digital Transformation through Digital Competence at the Regional Civil Service Agency of Banten Province. This research uses a survey method with a quantitative approach. The survey research used is intended to explain causal relationships and test hypotheses. This research focuses on uncovering causal relationships between variables.The results showed that Transformational Leadership had a positive and significant effect on Employee Engagement, with a path coefficient (β) of 0.960, a t-statistic of 122.029 (> 1.96), and a p-value of 0.000 (< 0.05). Transformational Leadership also had a positive and significant effect on Digital Competence, with a path coefficient (β) of 0.863, a t-statistic of 31.290 (> 1.96), and a p-value of 0.000 (< 0.05). Employee Engagement and Digital Competence each had a positive and significant effect on Digital Transformation, with path coefficients (β) of 0.484 and 0.298 and t-statistics of 5.546 and 3.715, respectively (p < 0.05). Transformational Leadership also had a positive and significant effect on Digital Transformation, with a path coefficient (β) of 0.221, a t-statistic of 2.810 (> 1.96), and a p-value of 0.005 (< 0.05). Furthermore, Employee Engagement and Digital Competence significantly mediated the effect of Transformational Leadership on Digital Transformation, with path coefficients (β) of 0.465 and 0.257 and t-statistics of 5.487 and 3.502, respectively (p < 0.05). This study concluded that Transformational Leadership played an important role in strengthening Digital Transformation, both directly and indirectly through enhancing Employee Engagement and Digital Competence at the Regional Civil Service Agency of Banten Province.